Randomized clinical trial between Fluoxetine and Dapoxetine treatment among premature ejaculation’s men and its effect on marital satisfaction - Che' Man, Mohamad; Mohd Zain, Faridah; Che Alhadi, Shahidah; Yaacob, Najib Majdi; Ismail, Shaiful Bahari (International Islamic University Malaysia, 2021)
Introduction: Premature ejaculation(PE) decreases sexual pleasure and quality of life, and both Fluoxetine and Dapoxetine were used in PE therapy. Dapoxetine is the first SSRI with short half-life and less side effects, primarily designed for PE therapy. Aims: To evaluate and compare the effects of Fluoxetine and Dapoxetine on PE symptoms and marital satisfaction. Methods: 44 participants aged between 18 and 64 with a PEDT score of ≥9 from Hospital USM's Primary Care Clinic, Kelantan Malaysia were selected and randomized into two groups: Fluoxetine(FG) and Dapoxetine Group(DG), and administered for 8 weeks with either regular Fluoxetine(20mg) or Dapoxetine (30mg) on demand at least once a week. Main Outcome Measures: Premature Ejaculation Diagnostics Tool(PEDT) score were used to assess PE symptoms and Dyadic Satisfaction-Dyadic Adjustment Scale(DS-DAS) used to evaluate marital satisfaction at baseline and at the 8th week. RESULTS: 22 and 21 participants in FG and DG completed the study. For both groups PEDT scores decreased substantially [from 11.41 to 5.45(P<0.001) among FG, from 13.43 to 3.10(P<0.001) among DG]. After adjustment of the baseline PEDT score, PEDT scores in DG(6.03 vs 2.49, P<0.001) were lower at 8th week. Both groups showed significantly improved DS-DAS scores [from 34.50 to 40.68(P<0.001) in FG, from 36.57 to 44.33(P<0.001) in DG]. No marked difference in DS-DAS scored after adjustment of the baseline DS-DAS score(41.13 vs 43.86, P=0.055) at the end of assessment. CONCLUSION: Treatment of PE with either Fluoxetine or Dapoxetine decreases PE symptoms and increases marital satisfaction.